Clinico-microbiological analysis of bactibilia isolates in patients of cholecystectomy - Katyal, Ashima; Bala, Kiran; Bansal, Anand; Chaudhary, Uma (International Journal of Research in Medical Sciences, 2017)
Background: The current study determined microbial flora in bile aspirates from patients undergoing cholecystectomy along with antibiotic susceptibility pattern and resistance mechanism viz. extended spectrum β-lactamase (ESBL). Methods: The study included 110 such patients which were divided in three groups as: Group A that included acute cholecystitis with or without cholelithiasis, Group B included chronic cholecystitis with or without cholelithiasis and Group C included other hepatobiliary ailments requiring cholecystectomy viz. gallbladder carcinoma, acute emphysematous gall bladder and mucocele gall bladder. The bile was subjected to complete microbiological and histopathological examination. Antimicrobial susceptibility of the isolates was performed as per CLSI guidelines. Results: Bacteria were recovered from 07 samples (20%) in Group A, 17 (48.57%) in Group B and 11 (31.43%) in Group C. The polymicrobial infection was seen in 04 (11.43%) patients. The most common organisms isolated were Escherichia coli 15 (38.46%), Klebsiella pneumoniae and Pseudomonas aeruginosa 8 (20.51% each). The majority of Enterobacteriaceae isolates were susceptible to piperacillin-tazobactam and carbapenems. The ESBL production was observed in 17 (43.58%) isolates. Conclusions: Therefore, antimicrobial susceptibility of potential causative organisms, presence of resistant strains in bile, the severity of the cholecystitis, and the local susceptibility pattern must be taken into consideration while prescribing antibiotics. A protocol regarding the management of such cases should be formulated based on observations of similar studies.